2015
DOI: 10.1186/s13071-015-0988-x
|View full text |Cite
|
Sign up to set email alerts
|

The formation of egg granulomas in the spleens of mice with late Schistosoma japonicum infection alters splenic morphology

Abstract: BackgroundSplenomegaly is a characteristic symptom of schistosome infection. Unlike the well known hepatic pathology of schistosomiasis, splenomegaly has received little scientific research and is generally considered to be a non-specific congestion caused by increased blood pressure within the venous sinuses. Moreover, to date, few studies have reported the deposition of schistosome eggs in the spleen. In a previous study, however, we observed that prolonged S. japonicum infections destroyed the structure of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
13
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 31 publications
3
13
0
Order By: Relevance
“…Some cells with many dilated cisternae of rough endoplasmic reticulum denoting activated cells secreting cytokines and cells with degenerative changes were also detected. These results were in accordance with [21,22] who explained that eggs deposition constitutes the major pathogenesis of schistosomiasis, with egg-laying beginning four weeks after infestation and reaching a peak at eight weeks post-infestation. Furthermore, Skelly [23] postulated that in contrast to the adult worms, parasite eggs via soluble egg antigen (SEA) provoked a potent chemotactic activity and strong inflammatory reaction resulting in stimulation of inflammatory cells and cytokines (including interferon-γ, TNF-α and ILs).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Some cells with many dilated cisternae of rough endoplasmic reticulum denoting activated cells secreting cytokines and cells with degenerative changes were also detected. These results were in accordance with [21,22] who explained that eggs deposition constitutes the major pathogenesis of schistosomiasis, with egg-laying beginning four weeks after infestation and reaching a peak at eight weeks post-infestation. Furthermore, Skelly [23] postulated that in contrast to the adult worms, parasite eggs via soluble egg antigen (SEA) provoked a potent chemotactic activity and strong inflammatory reaction resulting in stimulation of inflammatory cells and cytokines (including interferon-γ, TNF-α and ILs).…”
Section: Discussionsupporting
confidence: 80%
“…Instead, the granulomas were replaced by leucocytic (eosinophils) infiltration. This was in accordance with other investigators [21] as they explained that as the disease advances from the acute to the chronic stage, granulomas decrease in both size and cellularity because of immune regulation. Classically, the host initially responds with a (Th1) response which was directed against initial stages of the parasite.…”
Section: Discussionsupporting
confidence: 78%
“…During the past few years, many studies have proven that through the expression of chemokines and the secretion of cytokines, the responses of Th17 cells dominate and play key roles in the host defence in response to S. japonicum . Because Th17 has become an important supplement to Th1/Th2 paradigm, we must ask the question of whether or not NP30 can direct Th17 differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…During the acute stage of S. japonicum infection, schistosome antigens induce Th1‐dominant cell‐mediated immune response in the host. During the chronic infection stage, Th1‐type cellular immunity shifts to Th2‐type cellular immunity . Particularly, some recent studies have revealed that Th17 cells play crucial roles in the pathology in schistosomiasis .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation